2014
DOI: 10.1164/rccm.201307-1349oc
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Risk of Incident Asthma in Adults. The CARDIA Study

Abstract: Rationale: Asthma is associated with depression, but the temporality of the association has not been established.Objectives: To examine the association between prevalent elevated depressive symptoms and incident asthma, and between prevalent asthma and incident elevated depressive symptoms in a cohort of young and middle-aged adults.Methods: We examined the longitudinal association between asthma and depressive symptoms bidirectionally in the Coronary Artery Risk Development in Young Adults (CARDIA) cohort. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 51 publications
(52 reference statements)
3
49
1
Order By: Relevance
“…A recent longitudinal study showed that depression (defined as a Center for Epidemiologic Studies Depression (CESD) scale score ≥16 and/or self-reported use of antidepressant medications) is associated with 1.26 times higher risk of incident (new-onset) asthma among U.S. white and African American adults (95% confidence interval for hazard ratio= 1.02 to 1.56) 25 . In another longitudinal study, African American women with a CESD scale score ≥33 had twice the risk of incident asthma as those with a CESD scale score <16 (which suggests no significant depression) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal study showed that depression (defined as a Center for Epidemiologic Studies Depression (CESD) scale score ≥16 and/or self-reported use of antidepressant medications) is associated with 1.26 times higher risk of incident (new-onset) asthma among U.S. white and African American adults (95% confidence interval for hazard ratio= 1.02 to 1.56) 25 . In another longitudinal study, African American women with a CESD scale score ≥33 had twice the risk of incident asthma as those with a CESD scale score <16 (which suggests no significant depression) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, a number of studies have documented fairly strong and consistent associations between reports of discriminatory treatment and depressive symptoms, as well as major depressive disorder (Barnes et al 2004, Brown et al 2000, Gee et al 2007, Lau et al 2013, McLaughlin et al 2010). Both major depression and elevated depressive symptoms have been implicated in the development of a wide range of clinical disease outcomes including, but not limited to, cardiovascular disease (Henderson et al 2013, Vaccarino et al 2007, Whooley & Wong 2013), diabetes (Golden et al 2008, Holt et al 2014), HIV (Ickovics et al 2001), and asthma (Brunner et al 2014, Coogan et al 2014b). Depression and elevated depressive symptoms have also been linked to several important health behaviors such as smoking (Breslau et al 1998), inadequate physical activity (Roshanaei-Moghaddam et al 2009), and sleep (Hall et al 2000, Tsuno et al 2005).…”
Section: Ongoing Controversies and Gaps In Knowledgementioning
confidence: 99%
“…It is the most common chronic respiratory disease in adults worldwide with a prevalence of 4-8% [1,2]. Adults with asthma have twice as high risk of also having depression or anxiety compared to the general population [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%